Wirebrush4SPAM: a novel framework for improving efficiency on spam filtering services. (18th June 2012) - Pérez‐Díaz, N.; Ruano‐Ordas, D.; Fdez‐Riverola, F.; Méndez, J.R.; Sicilia, Miguel‐Angel
SUMMARY This paper introduces Wirebrush4SPAM, a plug‐in‐based C framework specifically designed for the development of fast spam filters by assembling different antispam schemes and techniques. Wirebrush4SPAM can be used to (i) build, execute and deploy simple spam filters and (ii) develop new techniques that can be easily combined and tested to achieve more accurate antispam models. To construct custom filters, programmers should manage three key concepts: filtering functions, parsers and event listeners. The main features of Wirebrush4SPAM include (i) a plug‐in‐based design, (ii) cache support for developing new plug‐ins, (iii) a smart filter evaluation heuristic for improving filter execution, (iv) configurable rule scheduling and (v) support for domain specific rules. Moreover, Wirebrush4SPAM is 10 times faster than SpamAssassin, which stands for the most popular and highly extensible framework for spam filtering. Wirebrush4SPAM is an open‐source project licensed under the terms of GNU lesser general public license and both source code and documentation are publicly available at http://www.wb4spam.org/. Copyright © 2012 John Wiley & Sons, Ltd.